Biallelic MUTYH mutations can mimic Lynch syndrome - Morak, Monika (Nature Publishing Group, 2014)
The hallmarks of Lynch syndrome (LS) include a positive family history of colorectal cancer (CRC), germline mutations in the DNA mismatch repair (MMR) genes, tumours with high microsatellite instability (MSI-H) and loss of MMR protein expression. However, in ∼10–15% of clinically suspected LS cases, MMR mutation analyses cannot explain MSI-H and abnormal immunohistochemistry (IHC) results. The highly variable phenotype of MUTYH-associated polyposis (MAP) can overlap with the LS phenotype, but is inherited recessively. We analysed the MUTYH gene in 85 ‘unresolved' patients with tumours showing IHC MMR-deficiency without detectable germline mutation. Biallelic p.(Tyr179Cys) MUTYH germline mutations were found in one patient (frequency 1.18%) with CRC, urothelial carcinoma and a sebaceous gland carcinoma. LS was suspected due to a positive family history of CRC and because of MSI-H and MSH2–MSH6 deficiency on IHC in the sebaceous gland carcinoma. Sequencing of this tumour revealed two somatic MSH2 mutations, thus explaining MSI-H and IHC results, and mimicking LS-like histopathology. This is the first report of two somatic MSH2 mutations leading to an MSI-H tumour lacking MSH2–MSH6 protein expression in a patient with MAP. In addition to typical transversion mutations in KRAS and APC, MAP can also induce tumourigenesis via the MSI-pathway.